Implementation of Religion Values on Character Education for Grade 2 Students in Madrasah Aliyah Negeri 1 Ponorogo - Muhammad Mukhlas; tri wibowo (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2018)
Behold the man will be honored with a value of religious in character. The main purpose of Islamic education is to produce a good man, in achieving the objectives of such required processes and efficient methods in order that these objectives can be achieved to the maximum as desired. This research includes qualitative research (field) a descriptive qualitative. As for the data source of the principal, vice principal, teacher's education and teacher of curriculum part of Islam. To collect the data, researchers using three methods, namely: the method of interview and methods of observation and methods in analyzing its pegs, documentary data, researchers using theory, Miles and Huberman that includes three steps, namely: the collection data, data presentation, data reduction, and conclusion. The results of this research indicate that: the purpose of the implementation of religious values in class 2 MAN 1 make a Godly character of students, the value of a good religious in theory and practice in all student life and methods used religious value transformation There are two methods, namely: in the classroom includes faqs and discussion as for outside classes include education giving Education conditioning, educational advice and punishment.